Reconstruction of Legal Protection for Witnesses and Victims in Handling Extraordinary Crimes in Indonesia - Adhalia Septia Saputri; Fransiska Novita Eleanora (Asosiasi Dosen Muda Indonesia, 2026)
Legal protection for witnesses and victims is a crucial element in the criminal justice system, particularly in handling extraordinary crimes such as corruption, terrorism, and human trafficking. Although regulated by Law Number 31 of 2014 concerning Witness and Victim Protection, its implementation still faces various structural and normative obstacles. This study aims to analyze the effectiveness of legal protection and reconstruct an ideal protection model. The research method used is normative juridical with statutory and conceptual approaches. The results indicate that existing protection is suboptimal due to weak inter-institutional coordination, limited authority, and the lack of strengthened protection for whistleblowers and justice collaborators. Therefore, a reconstruction of the protection system based on restorative justice and institutional strengthening is necessary.